Nashville nights - Noll, Katherine; West, Tracey (New York : Grosset & Dunlap, 2008)
In Nashville for the next stop on their concert tour, Aly and AJ meet the Walker Sisters, who ask them to be in a video, but when the digital files of the video are stolen, Aly and AJ must find the thief to clear their own names.
Collectible guitar-pick charm attached to inside cover.
Keywords: Aly & A.J.; Aly & A.J.; Mystery and detective stories